1993
DOI: 10.1002/1097-0142(19930101)71:1<36::aid-cncr2820710107>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The expression of cytochrome P-450, epoxide hydrolase, and glutathione s-transferase in hepatocellular carcinoma

Abstract: Background. Cytochrome P‐450, epoxide hydrolase, and glutathione S‐transferase (GST) all play a key role in the metabolism of chemical carcinogens, mutagens, and various anti‐cancer drugs. All these functionally associated enzymes might be involved in both the development of hepatocellular carcinoma and in determining the anti‐cancer drug sensitivity of such tumors. Methods. The expression of two forms of cytochrome P‐450 (P‐450 IA and P‐450 IIIA), microsomal epoxide hydrolase, and three classes of cytosolic G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
2
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 27 publications
3
23
2
1
Order By: Relevance
“…The wild-type C1/C1 alleles were comparable in 83 of 91 (91%) patients with AA and 222 of 235 (94.5%) controls (NS). The respective prevalence in healthy controls was comparable to data from other studies that analyzed Caucasian patients (20,21,43). These data exhibit no association of p450-cyp2E1 polymorphism with a risk for AA in children.…”
Section: (51%) Controls (Ns)mentioning
confidence: 99%
See 1 more Smart Citation
“…The wild-type C1/C1 alleles were comparable in 83 of 91 (91%) patients with AA and 222 of 235 (94.5%) controls (NS). The respective prevalence in healthy controls was comparable to data from other studies that analyzed Caucasian patients (20,21,43). These data exhibit no association of p450-cyp2E1 polymorphism with a risk for AA in children.…”
Section: (51%) Controls (Ns)mentioning
confidence: 99%
“…A null genotype is characterized by the absence of the respective GST protein (38). The GSTM1 null genotype has been shown to be associated with an increased risk of smoke-induced cancers (39 -41), breast cancers (42), and hepatocellular carcinoma (43,44). The GSTT1 null genotype has been shown to be associated with an increased risk for MDS (44 -46).…”
mentioning
confidence: 99%
“…Tumour and adjacent non-tumour tissue of HCC cases also showed interindividual variation in staining intensity. Variable expression of both CYP1A and 3A in primary malignant liver tumours by Western blot (Kirby et al 1993), immunohistochemistry (Murray et al 1993) and in situ hybridization (McKinnon et al 1991) has been observed previously.…”
Section: Discussionmentioning
confidence: 99%
“…The staining pattern observed in this study, a diffuse cytoplasmic immunoreactivity for tumour tissues, was similar to that found in a previous study (Murray et al 1993). Both tumour and adjacent non-tumour tissues showed loss of normal lobular structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation